Acute periodontal lesions (periodontal abscesses and necrotizing periodontal diseases) and endo‐periodontal lesions. (21st June 2018) - Herrera, David; Retamal‐Valdes, Belén; Alonso, Bettina; Feres, Magda
Abstract: Objective: To critically evaluate the existing literature on acute lesions occurring in the periodontium (periodontal abscesses [PA], necrotizing periodontal diseases [NPD], and endo‐periodontal lesions [EPL]) to determine the weight of evidence for the existence of specific clinical conditions that may be grouped together according to common features. The ultimate goal is to support an objective classification system. Importance: Although PA, NPD, and EPL occur with relatively low frequency, these lesions are of clinical relevance, because they require immediate management and might severely compromise the prognosis of the tooth. Findings: In general, the evidence available to define these three conditions was considered limited. PA and EPL are normally associated with deep periodontal pockets, bleeding on probing, suppuration, and almost invariably, with pain. EPL are also associated with endodontic pathology. NPDs have three typical features: pain, bleeding, and ulceration of the gingival interdental papilla. The available data suggested that the prognosis of PA and EPL are worse in periodontitis than in nonperiodontitis patients. Lesions associated with root damage, such as fractures and perforations, had the worst prognosis. NPD progression, extent and severity mainly depended on host‐related factors predisposing to these diseases. Conclusions: PA should be classified according to the etiological factors involved, with the most frequent being those occurring in pre‐existing periodontal pockets. NPD are clearly associated with the host immune response, which should be considered in the classification system for these lesions. EPLs should be classified according to signs and symptoms that have direct impact on their prognosis and treatment, such as presence or absence of fractures and perforations, and presence or absence of periodontitis.